2021
DOI: 10.22265/acnef.8.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infección por Cryptococcus neoformans en paciente trasplantado renal con COVID-19. Reporte de caso.

Abstract: La infección por el síndrome respiratorio agudo severo por coronavirus 2 (SARS-CoV-2), causante de la enfermedad COVID-19, representa una de las emergencias sanitarias más deletéreas de las últimas dos décadas; de la que aún existen innumerables incógnitas acerca del curso y manejo de presentaciones atípicas. Por lo anterior, resulta importante publicar casos clínicos de interés en población especial como lo son los pacientes receptores de trasplante renal quienes pueden tener un mayor riesgo de contraer la en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Of the total number of patients, the male sex was affected in 48 cases while the median age was 60 years, with statistically significant differences between the two groups: alive versus dead in both variables ( p value = 0.0203 and 0.0332, respectively). Of 60 patients with available information, 31 were from the United States 15 , 16 , 19 40 (51.6%), 8 from Peru 41 (13.3%), 7 from Brazil 14 , 42 47 (11.6%), and 2 from India 48 , 49 and Italy 50 , 51 (3.3% each), while the rest were from Canada, 52 Colombia, 53 China, 54 the Czech Republic, 55 the UK, 56 Uganda, 57 Qatar, 58 Lebanon, 59 Spain, 60 and Germany 61 ( n = 1; 1.7% each).…”
Section: Resultsmentioning
confidence: 99%
“…Of the total number of patients, the male sex was affected in 48 cases while the median age was 60 years, with statistically significant differences between the two groups: alive versus dead in both variables ( p value = 0.0203 and 0.0332, respectively). Of 60 patients with available information, 31 were from the United States 15 , 16 , 19 40 (51.6%), 8 from Peru 41 (13.3%), 7 from Brazil 14 , 42 47 (11.6%), and 2 from India 48 , 49 and Italy 50 , 51 (3.3% each), while the rest were from Canada, 52 Colombia, 53 China, 54 the Czech Republic, 55 the UK, 56 Uganda, 57 Qatar, 58 Lebanon, 59 Spain, 60 and Germany 61 ( n = 1; 1.7% each).…”
Section: Resultsmentioning
confidence: 99%
“…Cryptococcus neoformans is an encapsulated yeast-like fungus that is considered an opportunistic and rare pathogen in transplant recipients [ 50 ] and can cause cryptococcosis in immunocompromised patients. The most frequent and severe form of presentation is infection of the central nervous system, manifesting as subacute or chronic meningitis and characterized by headache, nausea, vomiting, fever, and altered consciousness; pulmonary, skin, lymph node, or other organ involvement may also occur to a lesser extent [ 66 ].…”
Section: Coinfections With Fungimentioning
confidence: 99%
“…Therefore, it can be said that coinfection with SARS-CoV-2 and Cryptococcus is rare. For example, in 2021, among 293 patients in a case study conducted in China, there was only one case reported [ 50 , 66 ]. However, it should be taken into account that SARS-CoV-2 infection may be an etiology for fungal infection by Cryptococcus neoformans due to the great multisystemic impact and the multiorgan dysfunction established by the viral agent, as the main cause of immunosuppression predisposing to infections by this microorganism.…”
Section: Coinfections With Fungimentioning
confidence: 99%